2012
DOI: 10.1111/j.1399-6576.2012.02686.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ICU survivors: a comprehensive review. The role of patient‐reported outcome studies

Abstract: Problems survivors face after intensive care unit (ICU) discharge begin while they are still in the ward, where many of their specific problems may run unrecognized, but they assume a heavy weight when they arrive at their homes and face several kind of limitations, from being unable to climb stairs because of weight loss, asthenia, dyspnea or joint stiffness to anxiety, depression or post-traumatic stress disorder. Follow-up consultations have given us a better understanding of these specific problems, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 81 publications
1
45
0
Order By: Relevance
“…[8][9][10] A study 8 of patients with multiple organ failure in 22 ICUs in the United Kingdom indicated that diminished HRQOL had an adverse effect on family employment and income; one-third of the families required support from government sources. In addition, one-quarter of the patients had decreased independence in activities of daily living and an increase in the use of health services.…”
Section: Contrast the Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…[8][9][10] A study 8 of patients with multiple organ failure in 22 ICUs in the United Kingdom indicated that diminished HRQOL had an adverse effect on family employment and income; one-third of the families required support from government sources. In addition, one-quarter of the patients had decreased independence in activities of daily living and an increase in the use of health services.…”
Section: Contrast the Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…These problems occur in up to 15% and 20% of the patients, respectively (Griffiths et al, 2007;Tully, 2012), and may hamper full recovery (Granja et al, 2012;McKhann et al, 1997;Pirraglia et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce principally modifiable risk factors several strategies are illustrated, including well-reflected intensive care sedation and analgesia, special prophylactic medication regarding the major risk of traumatic memories and posttraumatic stress disorder (PTSD), psychological and psychotherapeutic interventions in states of increased acute stress symptoms and aids for personal memories and reorientation. [30]. Persistierende Neuropathien ("critical illness neuropathy", CIP) und Myopathien ("critical illness myopathy", CIM) nach intensivmedizinischer Behandlung werden als eigenständige neurologische Spätfolgen beschrieben [32].…”
Section: Posttraumatische Belastungsstö-rungenmentioning
confidence: 99%